Variations in the Behavior of Pigs During an Open Field and Novel Object Test - Haigh, Amy; Chou, Jen-Yun; O'Driscoll, Keelin (Frontiers in Veterinary Science, 2020)
Tail biting is a serious welfare concern in pig production. It not only causes distress for victims, but may occur where pigs are unable to cope, and become biters. An animal’s ability to cope with stressful situations may vary between individuals, but the behavioural response could be consistent across different fear eliciting situations. We exposed 75 pigs to open field (OF) and novel object (NO) tests at 14 weeks of age. Within each pen of pigs (n = 16 pens, 55 pigs / pen), 6 pigs were selected for testing using the following criteria: 3 pigs that had severe bite wounds (BITTEN), 1 confirmed biter (BITER), 1 pig which could be easily approached and trained to provide a saliva sample (BOLD) and 1 pig which was extremely evasive, and was unable to be trained to willingly provide a saliva sample (SHY).Given that responses may be consistent in different scenarios, we hypothesised that SHY pigs would display more characteristics of a fear response (i.e. less movement in the open field, more time spent by the door, and longer latency to approach the novel object) than human BOLD pigs. We also hypothesised that BITTEN pigs would behave similarly to SHY and BITERS similarly to BOLD. The BOLD and BITER pigs spent more time exploring (P < 0.05) and less time by the door (P < 0.01) than the BITTEN and SHY pigs. Although there was an overall increase in cortisol level from before to after the tests (P < 0.001), this was only significant for BITTEN (P < 0.001) and SHY (P < 0.05) pigs. Therefore, as hypothesised, for several measures, BOLD and BITER pigs behaved similarly, and differently to SHY and BITTEN. However the low sample size potentially meant that for several measures, although numeric differences were in the direction hypothesised, there were no statistical differences. Further work in which a greater number of BITER pigs were included in the sample, may elucidate our hypotheses more clearly, as to whether responses to fear tests in pigs could be associated with the likelihood of being a tail biter, or victim.